2018
DOI: 10.2196/10202
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Evaluate the Effects of Internet-Based Digital Health Interventions for Citizens: Systematic Review of Reviews

Abstract: BackgroundDigital health can empower citizens to manage their health and address health care system problems including poor access, uncoordinated care and increasing costs. Digital health interventions are typically complex interventions. Therefore, evaluations present methodological challenges.ObjectiveThe objective of this study was to provide a systematic overview of the methods used to evaluate the effects of internet-based digital health interventions for citizens. Three research questions were addressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 48 publications
1
45
2
1
Order By: Relevance
“…In general, smart assistants have been evaluated for their response accuracy [ 5 ] and their general usability [ 6 ]. While considerable research has been conducted assessing digital health approaches, such as text message–based approaches and mobile apps for a range of health behaviors [ 7 - 9 ], few have included smart assistant responses to health-related queries. For instance, a pilot study comparing two smart assistants (Google Assistant and Apple Siri) to a standard Google Search on the topic of smoking cessation resources found that Google Assistant provided a greater number of evidence-based responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, smart assistants have been evaluated for their response accuracy [ 5 ] and their general usability [ 6 ]. While considerable research has been conducted assessing digital health approaches, such as text message–based approaches and mobile apps for a range of health behaviors [ 7 - 9 ], few have included smart assistant responses to health-related queries. For instance, a pilot study comparing two smart assistants (Google Assistant and Apple Siri) to a standard Google Search on the topic of smoking cessation resources found that Google Assistant provided a greater number of evidence-based responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 In health services where portals have been successfully implemented, patient access to their health records and messaging has been reported to improve communication, patient understanding of health information, engagement and selfmanagement, as well as sharing biomedical information that may result in greater patient safety. 23,24,[35][36][37] There is no evidence of portals causing increased concern or anxiety among patients. 35 However, providing patients with access to health records might interfere with doctors' collection of psychosocial and emotional information, leading to a call for improvements so that portals and EHRs can capture useful data without disturbing patients' and physicians' ability to communicate.…”
Section: Discussionmentioning
confidence: 99%
“…We will consider the following ‘Problem, Intervention, Comparison, Outcomes’ elements: (P): three targeted chronic diseases (diabetes, high blood pressure, dyslipidaemia), alone or combined; (I) all eHealth interventions implemented in primary care and that directly involve patients (eg, electronic medical records (EMRs), patient diary, patient portal, specific computerised monitoring for a chronic disease and technological interventions focused on lifestyle modifications; (C): routine follow-up; (O): health outcomes specific to the disease (eg, glycosylated hemoglobin (HbA1c) for diabetes), generic health outcomes (eg, mortality, quality of life), patient outcomes (eg, involvement, personal efficacy) and practices and process outcomes (eg, test numbers, emergency visits, hospitalisations). First, we will start to consult existing systematic reviews, in particular, that of Irizarry et al ,38 and a review of reviews that we have already completed 49. We will also document issues relating to needs, expectations and concerns in terms of eHealth solutions for patients, their informal caregivers and healthcare providers.…”
Section: Methods and Analysismentioning
confidence: 99%